Enological potential of grapes produced in different periods in a tropical region of Northeast Brazil. - PEREIRA, G. E. (2008)
The Lower-Middle São Francisco river Valley is a new vitivinicultural region located in northeast Brazil, between 8° and 9° S latitude. ln this region 11's possible to have two-three harvests a year, mainly due to an annual average temperature of 26.4°C, with about 567 mm of rainfall between January and April, altitude of 350 m above sea leveI and use of drip irrigation. There is';a. continuous vegetative developrnent and grapevine growth occurs throughout the whole year. Grap~ composition can vary strongly according to harvest time of the year due to different climatic conditions. Wineries harvest grapes for winemaking between May and December. The aim of t4~~ study was to compare Tempranillo grapes composition harvested in two periods: June and December 2007, to best understand the influence ofharvest date on grape quality.